Prototype design and modeling of active-loaded differential amplifier using Double-Gate MOSFET - Suvashan Pillay; Viranjay M. Srivastava (SN Applied Sciences, 2023)
Abstract This research work designs a prototype of an active-loaded differential amplifier using Double-Gate (DG) MOSFETs. The following text outlines the prototype design with testing in developing the conceptual understanding of the differential amplifier and its design requirement. This designed model uses mathematical models while assessing possible limitations of the amplifier and the DG MOSFET. The designed amplifier exhibits a differential gain of 4 V/V, with a bandwidth of 1 MHz. The common-mode output and gain values were tested, along with the resultant CMRR to assess the overall performance of the differential amplifier designed. Article Highlights An active-loaded differential amplifier using Double-Gate (DG) MOSFETs has been designed using hardware circuits. The designed amplifier exhibits a differential gain of 4 V/V, with a bandwidth of 1 MHz. The common-mode output and gain values have been tested, along with the resultant CMRR to assess the overall performance of the designed differential amplifier.